The Balkans: Old, New Instabilities - Giorgio Fruscione (Pubblicazioni ISPI, 2020)
2020 could be a crucial year for the Western Balkans. For over twenty years, the region has been stuck in a never-ending transition. Politics, economics, and geopolitics are still falling prey to old and new sources of instability. With the path towards EU integration still uncertain, many governments in the region are marked by autocratic tendencies, and international actors strive for a bigger say in the region. NATO is expanding to the Balkans, but regional security still depends on foreign soft power and influence. And while recipes for economic transition focus mainly on foreign direct investments that often lack transparency, Balkan societies are losing their citizens to substantial emigration. What are the factors contributing to Western Balkans instability in the age of Covid-19? Will the region continue to be ground for renewed geopolitical competition? How can the Balkans leave the transition phase and find a sustainable, balanced path onwards?